Multi-Criteria Analysis Method For Determining The Priority of Bridge Construction - Meillyta, Meillyta; Fatimah, Aldina; Zulfahmi, Zulfahmi (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2023)
Bridge is one of the important infrastructure facilities which functioned to connect roads that support the development of social and economic in a region. In Indonesia, each year, the limited fund is available to accommodate all construction projects.  In practice, the government of Aceh Besar District has limited District Revenue and Expenditure Budgets (APBK) to finance the entire project of bridge construction. Considering that many other sectors still require APBK funding, the priority rank of the bridge development needs to be determined. This study aims to identify the dominant criteria in determining the development of bridges and the priority rank of bridge development projects. This study used a mixed method approach which is a qualitative and quantitative method. The Qualitative method is related to respondent perception through distributing questionnaires and the qualitative method is related to numbers used through the perception score of respondents from the analysis.  Respondents are stakeholders and policymakers as many as 8 people. The questionnaire contains some criteria, namely the length of the bridge, construction costs, land use, accessibility, population, and regional development. Based on the literature review, those criteria can be used to obtain which bridge needs to be prioritized. Multi-Criteria Analysis is used to analyze those criteria from respondent perception. The results show that the dominant criteria in determining the construction of bridges in the project were construction costs with a weight of 0.35. It is also obtained that the bridge development project at first rank is the Kr. Keumeuruek with a value of 7.56.